Barriers to orthodox medical care of prostate cancer in Ghana - Patrick Opoku Manu Maison; Prince Arkoh; Ahmed Sani; Emmanuel Ekow Mensah-Baidoo; Gifty Owusu; Esther Yeboah Danso; Nana Benyin Koufie; Susanna Andzie; Perez Gyamfi; Emmanuel Omane; Sylvester Antwi; Nallasivam Palanisamy; et al. (Scientific Reports)
Abstract Traditional medicine is widely used in sub-Saharan Africa, particularly in Ghana, where it is commonly integrated with modern orthodox medicine. This study examines the barriers that delay the pursuit of orthodox medical care for prostate cancer (PCa) in Ghana’s Central region, where a blend of traditional and modern orthodox medicine exists. The preference for indigenous traditional medicine often results in late-stage presentations of PCa, adversely affecting patient outcomes. This prospective cross-sectional study was conducted from July to December 2022 at the Cape Coast Teaching Hospital (CCTH) and in four local communities. We investigated why men prefer traditional over orthodox medicine and identified cultural beliefs, attitudes, and gaps in health awareness that contribute to delays in diagnosing and treating PCa. The study involved administering questionnaires, providing education on PCa, and conducting free prostate-specific antigen (PSA) screening. Ethical approval was obtained from the Ethics Research Committee of the Ghana Health Service. A total of 282 patients participated, including 268 men from the communities and 14 diagnosed with PCa at CCTH after initially consulting traditional healers. Of the community-recruited patients who underwent PSA testing, 26% had elevated PSA levels and underwent further diagnostic procedures. Ultimately, nine of 268 community patients were confirmed to have PCa. Most patients (57.4%) had limited education, which correlated with late presentations and various misconceptions about PCa. The study highlights significant cultural and economic barriers that lead to the late-stage presentation of PCa among men in Ghana’s Central region. There is a critical need for a culturally sensitive, multi-pronged strategy that enhances public education about the benefits of early diagnosis and fosters collaboration between traditional healers and orthodox healthcare providers to improve prostate cancer outcomes in Ghana.